(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
Sodium dodecyl sulphate (SDS) is an anionic surfactant which is mainly utilized in washing detergents and industrial products and solutions. Its toxicity and contamination of the surroundings environment are ubiquitous. In this study, the SDS-degradation capacity of a previously isolated molybdenum-reducing bacterium; Enterobacter sp. Strain Neni-13 is reported. At 1 g/L of SDS as the sole carbon source, the bacterium grew maximally at pH 7.0, the temperature range from 20 to 45 Â°C support maximal growth and require ammonium sulphate as the best nitrogen source at the optimal concentration of 1 % w/v. Growth on various concentrations of SDS as a carbon source shows that the bacterium can grow maximally in between 800 and 1200 mg/L and was able to grow at the maximum concentration of 1500 mg/L while concentrations higher than this caused the cessation of growth. The heavy metals mercury, silver and copper inhibit growth on SDS. The ability of this bacterium to detoxify dual toxicants, which include the degradation of high concentration of SDS is highly sought.